2020
DOI: 10.1021/acssuschemeng.0c07242
|View full text |Cite
|
Sign up to set email alerts
|

Process Simulation and Optimization of Ammonia-Containing Gas Separation and Ammonia Recovery with Ionic Liquids

Abstract: Ionic liquids (ILs) have been experimentally proved to be effective for ammonia-containing gas separation and recovery. A systematic strategy including thermodynamic models, process simulation, multiobjective genetic algorithm, and assessment for novel IL-based separation of ammonia-containing tail gas and ammonia recovery process was proposed. The conventional IL ([C4Mim]­[NTf2]) and the functional IL ([C4im]­[NTf2]) were selected, and their NH3 removal performance was investigated. Physical properties of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…The first study reported the NH 3 absorption process simulation and optimization using two [NTf 2 ]-based ILs compared with traditional water scrubbing. 136 The authors use a multiobjetive optimization with three different objective functions (TAC, CO 2 emissions and NH 3 recovery). A genetic algorithm (NSGA-II) is used along several decision variables (theoretical column stages, feed stage, solvent flow, pressure and temperature of flash regeneration).…”
Section: Nh 3 Absorptionmentioning
confidence: 99%
“…The first study reported the NH 3 absorption process simulation and optimization using two [NTf 2 ]-based ILs compared with traditional water scrubbing. 136 The authors use a multiobjetive optimization with three different objective functions (TAC, CO 2 emissions and NH 3 recovery). A genetic algorithm (NSGA-II) is used along several decision variables (theoretical column stages, feed stage, solvent flow, pressure and temperature of flash regeneration).…”
Section: Nh 3 Absorptionmentioning
confidence: 99%
“…Table summarizes the functional types and NH 3 absorption capacities of representative ILs reported in the literature. The process simulations performed by Zhan et al and Liu et al demonstrated that the IL-based NH 3 separation process exhibits significantly reduced energy consumption, operation cost, and net CO 2 emission than an aqueous-based process. , However, it should be pointed out that most ILs are expensive because they are normally synthesized from expensive reactants or through complicated routes. In addition, most ILs are with high viscosity due to the strong electrostatic attraction between cations and anions .…”
Section: Liquid Absorptionmentioning
confidence: 99%
“…ILs are of flexible designability in structures by adjusting the type of anion and cation, changing the length of the alkyl chain, or grafting functional groups on the cationic chain . The unique chemical structure makes ILs have low melting points, good thermal and chemical stability, high ionic conductivity, and adjustable polarity. , ILs have shown unique advantages in chemical synthesis, separation and extraction, and as electrolyte materials . In the synthesis of materials, ILs can be limited to the inorganic matrix to form the interpenetration of two continuous three-dimensional (3D) network structures, namely, an inorganic ionogel .…”
Section: Introductionmentioning
confidence: 99%